INVESTIGATION OF THE PRESENCE OF HUMAN PAPILLOMAVIRUS DNA IN VARIOUS GASTROINTESTINAL CARCINOMA SAMPLES - Erol, Deniz; Bulut, Yasemin; Yuce, Huseyin; Ozercan, Ibrahim Hanifi (Ankara Microbiology Soc, 2009)
The role of human papillomavirus (HPV) has been well established in the pathogenesis of cervical cancers. However, HPV-DNA has also been detected in tumor tissues of other malignancies. Recently, detection of HPV-DNA in gastrointestinal cancer tissues with in-situ hybridization and PCR technologies has suggested possible role of HPV in gastrointestinal cancers. In this study, it was aimed to investigate the presence of HPV in the tumor tissues and adjacent normal tissues of gastrointestinal cancers and to determine the types of HPV in positive cases. The study included a total of 106 (59 male, 47 female, age range: 25-80 years, mean age: 57.03 +/- 1.29 years) patients, of them 38 had gastric, 42 colon, 20 rectal, 4 esophageal and 2 small intestinal cancers. Genomic DNAs were isolated from the parafin embedded specimens of tumor and tumor-adjacent normal tissues and the performance of the extraction process was controlled with PCR using beta-globin primer. DNA extraction was achieved in 100 of the tumor tissues and in all of the tumor adjacent normal tissues (n= 106). HPV-DNA was searched by using GP5/GP6 primers and concensus PCR method. HPV-positive DNA samples were further typed by using HPV-11, 16, 18, 33 specific primers. HPV-DNA was detected in 41% (41/100) of tumor tissue samples and 31% (33/106) of tumor-adjacent normal tissue samples. There was no istatistically significant difference in terms of HPV-DNA positivity between tumor and tumor-adjacent normal tissues (p> 0.05). HPV-DNA was detected in 44.7% (33/106) of gastric samples, 35.1% (13/37) of colon samples, 47.3% (9/19) of rectal samples, 25% (1/4) of esophagus samples and 50% (1/2) of small intestine samples. Eight of the HPV positive tumor tissues revealed HPV type 16, three type 18 and five type 33, while three of normal tissue samples revealed type 18 and two type 33. Two different HPV types together were detected in two tumor samples, one being type 16 + type 33 and the other being type 18 + type 33. Although these results indicating the presence of HPV-DNA in gastrointestinal tumor and adjacent normal tissues, suggest a possible role of HPV in gastrointestinal tumors, further studies are necessary for the establishment of a definite causative role.
Keywords: Gastrointestinal cancer; human papillomavirus; HPV; PCR